Menggagas Budaya Inovasi Demi Tercapainya Organisasi Publik Berkinerja Tinggi - Nurlia Nurlia (Jurnal Transformasi Administrasi, 2016)
There are many reason why public organizations need for innovation. The most fundamental reason is due to the demand for accountability, transparency and good governance principles dribbling organizations to the higher performance. Innovation is an extremely powerful way to overcome the problem and bureaucratic deadlock. Therefore, public organizations should open up enough space for the growth of innovation by developing innovation culture. Developing such culture means accustoming to make a change, renewal and improvement in order to produce a better performance. They will improve the employees performance and eventually will improve organizational performance. To achieve a high performing public organizations, innovation product should have added-value and competitive advantages which can be felt by society, because public organizations aim at providing a satisfactory service to the community.